2016
DOI: 10.3846/btp.17.11124
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of earnings and prediction of future cash flows: the role of timely recognition of bad news

Abstract: Timely recognition of losses and expenses compared to revenues and increased values precipitates future expenses to match with current revenues. Thus, timely recognition of losses acts to reduce the persistence of earnings. However, it is expected that a more timely recognition of negative cash flows, as bad news, increase the power of earnings for predicting future cash flows. This study investigates the effects of the timely recognition of bad news (loss) versus the good news on the decrease of the persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…99 [ 6 ], pressure on management comes from outside the company and takes the form of needing to meet the demands and targets of third parties and having responsibility for outcomes. Consistent earnings are demanded [ 44 ]. Management that manipulates earnings faces greater pressure in respect of the company's financial stability, leverage, and financial targets [ 30 ].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…99 [ 6 ], pressure on management comes from outside the company and takes the form of needing to meet the demands and targets of third parties and having responsibility for outcomes. Consistent earnings are demanded [ 44 ]. Management that manipulates earnings faces greater pressure in respect of the company's financial stability, leverage, and financial targets [ 30 ].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Jelodari and Kordshouli (2016) suggested that earnings quality provided highly rigorous forecasts for operating cash flows. Kordestani et al (2016) proved that the timely loss recognition did not affect the persistence and the predictive ability of earnings in Iranian listed companies during the period of 2003-2010, which implied that accounting conservatism did not distort earnings quality. Carvalho, Camargo and Kalatzis (2017) suggested that earnings quality attributes, including earnings predictive ability, were good explicators of operational and market performance of Latin American companies over the period of 1989-2009.…”
Section: __________________________________________________________________________ 2021 / 35mentioning
confidence: 96%
“…In this case, annual earnings form the basis of estimating earnings persistence. When a firm's earnings possess the quality of persistence, it is more likely than not, to continue into the foreseeable future (Kordestani et al, 2016).…”
Section: Literature Review 21 Earnings Persistencementioning
confidence: 99%